Occupational Health and Safety Analysis Using the HIRARC Method at Mitsubishi DIPO Bukittinggi - Rival Handika; Milana Milana; Nuzul Hidayat; M. Yasep Setiawan; Reinny Patrisina (AEEJ : Journal of Automotive Engineering and Vocational Education, 2025)
Occupational safety is a critical concern in automotive workshop environments due to the high-risk nature of tasks such as engine repair, welding, and electrical diagnostics. This study investigates automotive workshop risks at the Mitsubishi DIPO Workshop in Bukittinggi by identifying hazards, assessing risk levels, and formulating workplace accident prevention strategies. The HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method was applied to evaluate 28 potential hazards, two of which were classified as extreme risks. Further analysis of these risks was conducted using the Fishbone Diagram to identify root causes across six contributing factors: human, machine, material, method, environment, and management. Based on these findings, targeted risk control measures were developed following the hierarchy of control, including engineering interventions, administrative policies, and personal protective equipment. This research demonstrates how integrated methods such as HIRARC and Fishbone Diagram can support comprehensive occupational safety planning and risk mitigation in automotive workshops.